Analysis the Causes of High Food Costs and Food Cost Control Strategies at the Food and Beverage Product Department at the Four Points Hotel by Sheraton Bali - Made Artajaya; Made Wahyu Chikara Wijaya; I Gusti Agung Febrianto (Politeknik Pariwisata Makassar, Indonesia, 2022)
The hotel's second largest revenue is food and beverage revenue. Four Points by Sheraton Bali Ungasan benefit from the sale of food and beverages, the income can be achieved maximally if the control of food cost effectively and efficiently. The objective of this study was to determine the cause of the high food cost at Four Points by Sheraton Bali Ungasan in 2020 and to determine the food cost control strategy by the food and beverage product department. Based on the percentage comparison between standard food costs and actual food costs period JanuaryDecember 2020, there is a difference of 4.03%. This study uses a qualitative descriptive analysis technique of triangulation of sources using the theory of Dittmer, Ojugo, and Wiyasha. The results of this study indicated the purchasing section was not applied standard purchase specifications and standard prices. The receiving section did not check the quality and quantity of food from suppliers. Foodstuff storage did not apply FIFO and the storage space did not mind the feasibility and temperature. The issuing section did not apply storeroom requisition. The kitchen section did not apply the standard yield, standard recipe and standard portion size optimally, this causes high food costs.